An optimized polyamine moiety boosts the potency of human type II topoisomerase poisons as quantified by comparative analysis centered on the clinical candidate F145121. Issue 76 (10th October 2015) - Palermo, Giulia; Minniti, Elirosa; Greco, Maria Laura; Riccardi, Laura; Simoni, Elena; Convertino, Marino; Marchetti, Chiara; Rosini, Michela; Sissi, Claudia; Minarini, Anna; De Vivo, Marco
<x xml:space="preserve">Abstract</x> Computational–experimental analyses explain F14512's boosted potency as a topoII poison.